Mencegah Kekerasan Seksual Pada Anak: Studi Implementasi Kebijakan Perlindungan Anak di Lampung Tengah Perspektif Siyasah Tanfidziyah - Resa, Andi; Frenki, Frenki; Alghifari, Abuzar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Child protection is a crucial step in efforts to realize child welfare. The government needs to show greater seriousness in implementing child protection policies, especially related to cases of sexual violence against children. This study aims to determine the extent to which the Central Lampung Regency Government exercises its authority in implementing child protection policies related to Siyasah Tanfidziyah. The type of research is field research conducted at the Women's Empowerment and Child Protection Service of Central Lampung Regency, with a qualitative approach. Primary data are collected through interviews with the Women's Empowerment and Child Protection Service of Central Lampung, as well as with victims and their parents. Secondary data are sourced from books, journals, and other relevant documents. The author's data collection technique uses interview and documentation methods. Furthermore, the data is analyzed using descriptive techniques. Based on the results of the study, the government has taken various steps to prevent violence against children, including through education and socialization to the community about the dangers of sexual violence. However, the implementation of these efforts still faces several obstacles, such as budget limitations that hinder the program's reach to all regions, especially considering the large geographical conditions of Central Lampung Regency. In addition, the low level of public awareness of the importance of child protection, especially from sexual violence, is also a challenge in itself.